5 Lanes 5 Fingers Portable Touch-Typing Interface "ParoTone" for Efficient Sensorimotor Learning: Musical Performance Acquisition Much Faster than Piano - Mita, Shinjiro; Sato, Nayuta; Fujimoto, Morio; Sugimoto, Shunichi; Fujimoto, Taiga; Ozawa, Makoto; Fukunaga, Hiroki; Mita, Zenjiro; Iwasaki, Satoru (International journal of human-computer interaction, 2023)
Being able to play a musical instrument requires complicated sensorimotor learning. Many beginners give up practicing Piano or Guitar because they require a long time of practice to overcome difficulties. It is not possible to practice and perform Piano or Guitar anytime and anywhere. We fundamentally rethought how the device and software should be, and tested the hypothesis that a new interface "ParoTone" with music game style notation, one-to-one correspondence between 5 lanes and 5 fingers with octave shifts, playing chords with one button can balance the three elements: easiness to learn, a wide range of expression, and portability. We found that compared to Piano, ParoTone is portable and enables beginners to learn ∼3 times faster for melody, five times faster for chords. The ParoTone interface in the future may be useful not only for music but in other fields to learn to operate multiple commands in a timely manner.